Stress Analysis Of Stretchable Thermal Sensor - Lee, Mei Wen (Universiti Sains Malaysia, 2017)
This paper present a summary of the performance of modelling for stretchable circuit. For this new technology, the stretchable board can achieve mechanically bendable and stretchable by using the elastomer based substrate and interconnect. Hence, the study on mechanical properties of substrate effect on design of interconnect is important on the fatigue lifetime and reliability of circuit. Nowadays, the reliability of stretchable circuit is still an existing issue when it continuously supplied by cyclic stresses which will cause the elastic strain deformation during stretch and compress. The purpose of this paper is to present the stress and strain deformation on the interconnect design and reliability of stretchable circuit. By using the Finite Element Method (FEM), it enables to define a more reliable design and suitable material of the stretchable circuit. The stretchability performance can be evaluated on the strain and stress applied to the interconnect and substrate. Suitable material properties of substrate able to offer the less damage during elongation. PDMS and TPU are chosen as material of substrates because of its high elongation before break and it allows high stretchability. This study demonstrates the effect of stress and strain deformation on new design of stretchable board by using proposed material for the substrates at different elongation.